Studi Kriminologi terhadap Kejahatan Prostitusi Online Melalui Aplikasi MiChat Ditinjau dari Perspektif Anomie Theory (Studi Kasus Aplikasi MiChat) - Sakum, Sakum; Guntara, Deny; Abas, Muhamad (Wajah Hukum, 2024)
Online prostitution is the practice of prostitution conducted through digital platforms, such as messaging apps or social media, where sexual services are offered and transactions are managed online. Michat is an instant messaging app that allows users to communicate via text, voice, and video. In addition to basic features like private and group chats, Michat also provides options for media sharing and finding new friends. However, this app is sometimes misused for illegal activities such as online prostitution. This study uses a qualitative method with a case study approach to explore how Michat serves as a medium for this crime and how social, economic conditions, and changes in societal values contribute to the phenomenon. The findings of this research suggest that Anomie Theory explains how social disorder and the decline of norms can contribute to the emergence of deviant behavior, including online prostitution. Additionally, the study provides in-depth insights into the causes of online prostitution and offers recommendations for more effective prevention and intervention measures by the government.